Structural and mutagenesis studies of the NS3 helicase from dengue virus for drug discovery - Yang, Xiaoqing (2009)
With reference to the structure analysis of RNA unwinding mechanism coupled with ATP hydrolysis by Dengue virus (DEN) non-structural 3 (NS3) protein (Luo et al., 2008a), site-directed mutagenesis on DEN NS3 helicase domain was performed. Five residues conserved among Flaviviridae were selected for mutation and six soluble mutant proteins were generated. RNA stimulated ATPase activity and RNA helicase activity were determined. Residue D290 resides in subdomain I and is able to form a direct contact to RNA. Mutation D290A presented significantly reduced ATPase activity and enhanced helicase activity. Residue L429 resides in a F hairpin of subdomain II. It pairs with A444 to form a hydrophobic patch, which was proposed to disrupt base stacking at RNA unwinding fork. Mutation L429V enhanced helicase activity. A455 resides in VI motif at subdomain II and was suggested to form a part of phosphate exit route. Mutations A455I and A455T diminished ATP hydrolysis activity. Protein activities were further discussed in a structure-based manner. The study might be useful for future investigation on DEN NS3 and antiviral drug design.